If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2y-2)=4(2y+1)
We move all terms to the left:
3(2y-2)-(4(2y+1))=0
We multiply parentheses
6y-(4(2y+1))-6=0
We calculate terms in parentheses: -(4(2y+1)), so:We get rid of parentheses
4(2y+1)
We multiply parentheses
8y+4
Back to the equation:
-(8y+4)
6y-8y-4-6=0
We add all the numbers together, and all the variables
-2y-10=0
We move all terms containing y to the left, all other terms to the right
-2y=10
y=10/-2
y=-5
| -2x^2+480x=0 | | 12x+15=-3x-90 | | 3+5x=4x+10 | | 2x+1=6x+19 | | 420=x^2=26x | | 6+3x=5x-10 | | 8x+(4-2)+3=3x-2(7+4x)+11 | | 3c-9=(-27) | | x(x+13)=-12 | | 6x6=36 | | 3.14x6x=4396 | | 5x+3(x+4)=9 | | 45x+80x=8040 | | 5-12y=3y | | 45+x+x=80 | | 50=2u+10 | | 1.4(y-5)-0.2=0.5(6y-8) | | 1x+72=32 | | Y=2.6x+3.1 | | 1/3(-9x-3)=11 | | 4d=3d–7 | | 4^(x+1)+2^(x+1)=72 | | 5^9/5^t=5^-3 | | 12*2(7r=)6 | | 2(-8-k)=-2k-11 | | 4x+5=9x-155x | | 11y=4÷11 | | |x-6|=8 | | Y=3x+-27 | | x+1/4=13 | | 3(5x−7)=24 | | 6x-2=5(4x+8) |